DEIA is essential to advance the goals of translational science: Perspectives from NCATS. Issue 1 (9th November 2023) - Hussain, Shadab F.; Vogel, Amanda L.; Faupel-Badger, Jessica M.; Ho, Linda; Akacem, Lameese D.; Balakrishnan, Krishna; Geiger, Rebekah; Gopal-Srivastava, Rashmi; Haynes, Brittany; Hodges, Marcus G.; Isler, Tanetta; Mathé, Ewy A.; et al.
Abstract: The National Center for Advancing Translational Science (NCATS) seeks to improve upon the translational process to advance research and treatment across all diseases and conditions and bring these interventions to all who need them. Addressing the racial/ethnic health disparities and health inequities that persist in screening, diagnosis, treatment, and health outcomes (e.g., morbidity, mortality) is central to NCATS' mission to deliver more interventions to all people more quickly. Working toward this goal will require enhancing diversity, equity, inclusion, and accessibility (DEIA) in the translational workforce and in research conducted across the translational continuum, to support health equity. This paper discusses how aspects of DEIA are integral to the mission of translational science (TS). It describes recent NIH and NCATS efforts to advance DEIA in the TS workforce and in the research we support. Additionally, NCATS is developing approaches to apply a lens of DEIA in its activities and research – with relevance to the activities of the TS community – and will elucidate these approaches through related examples of NCATS-led, partnered, and supported activities, working toward the Center's goal of bringing more treatments to all people more quickly.